PEMANFAATAN TEPUNG BIJI NANGKA UNTUK PEMBUATAN KUE NASTAR DAN NILAI GIZINYA - Yosua Festus Sitorus; Evawany Y Aritonang; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
To help reduce dependence on wheat flour and lower the selling price, the use of flour can be reduced by the use of other ingredients. Substitution of wheat is expected to guarantee the sustainability of production and simultaneously empower the potential of local resources such as jackfruit seeds. Utilization of jackfruit seeds is still relatively low. This can be seen from the public consumption of jackfruit seed itself, where the processed only consumed in the form of simple preparations such as boiled just like that. Though the utilization of jackfruit seeds can be developed again into a variety of processed products that are varied and more interesting. The reason for the selection of jackfruit seeds as raw material for making this nastar cake is because jackfruit seeds are superior when compared to other similar fruit seeds (Cempedak Seeds and Durian Seeds) in terms of nutritional value, ethics, and aesthetics as food raw materials. Jackfruit seed is very possible to be processed into flour because of the composition of large starch. There were two treatments applied in this study, the first nastar cake made with a 50 percent ratio of jackfruit flour to 50 percent wheat flour, the second a nastar cake made with a ratio of 70 percent jackfruit flour and 30 percent wheat flour. Then compared also the nutrients in it. Furthermore, receive power test to see the level of preference for each cake nastar. After tested through Laboratories research with test parameters determined sequentially in 100 grams of nastar cake with Comparison of jackfruit seed flour and wheat flour 50:50 and 70:30 value as follows: Carbohydrates as much as 40.1 grams and 40.9 grams, Fat As much as 20.0 grams and 19.5 grams, Protein A total of 5.71 grams and 6.09 grams, Fospor of 0.17 grams and 0.20 grams, Calcium as much as 45.9 mg and 30.3 mg. The use of jackfruit and wheat flour for making nastar cake with 50:50 and 70:30 Comparison has no significant difference from Color, Aroma, Texture and Flavor. However, most Panellists prefer the Nastar cake with jackfruit seed flour and 50:50 wheat flour instead of Nastar Cake with ground jackfruit flour and 70:30 flour. Keywords: Jackfruit Seed Flour, Nastar, Acceptance Test, Nutritional Value.